PEG–MWCNT/Fe hybrids as multi-modal contrast agents for MRI and optical imaging. Issue 55 (20th May 2016) - Baranowska-Korczyc, Anna; Jasiurkowska-Delaporte, Małgorzata; Maciejewska, Barbara M.; Warowicka, Alicja; Coy, L. Emerson; Zalewski, Tomasz; Kozioł, Krzysztof K.; Jurga, Stefan
Abstract : This study examines the use of oxidized multi-walled carbon nanotube/iron (O-MWCNT/Fe) nanohybrids modified with polyethylene glycol (PEG) as multifunctional cellular imaging agents for magnetic resonance imaging (MRI) and fluorescence microscopy. Abstract : This study examines the use of oxidized multi-walled carbon nanotube/iron (O-MWCNT/Fe) nanohybrids modified with polyethylene glycol (PEG) as multifunctional cellular imaging agents for magnetic resonance imaging (MRI) and fluorescence microscopy. The PEGylated MWCNTs with embedded iron particles were investigated as T 2 -weighted contrast agents for MRI. The number of PEG molecules attached to the MWCNT surface was calculated. The PEG–MWCNT/Fe complex was characterized by transmission electron microscopy, scanning electron microscopy, Fourier transform infrared and Raman spectroscopies. Covalent surface modification of the MWCNTs improves their solubility and enables the attachment of further biomolecules to their surface. The PEGylated nanostructures were labeled with the MDC organic dye and internalized inside HeLa cells for cellular imaging. Additionally, the minimal cytotoxic effect of PEGylated complexes in comparison to non-PEGylated samples was measured using the WST-1 test and an In Cell Analyzer. A confocal microscopy study of the organelle morphology also confirmed that the HeLa cell morphology was unchanged after treatment with PEGylated MWCNTs.